2003
DOI: 10.1375/136905203765693816
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of a Male Twin on Birthweight of its Female Co-twin — A Population-based Study

Abstract: Fetal growth is influenced by various determinants, with males being heavier than females. It was recently suggested that female birthweight tends to be increased by the presence of a male co-twin. We evaluated this hypothesis in the Israeli population. We reviewed a retrospective population database of the 1993-1998 Israeli Birth Registry. We compared male birthweight in the male-male and malefemale combination sets and female birthweight in the femalefemale and male-female combination sets. We compared the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 17 publications
2
8
0
Order By: Relevance
“…We did not find a tendency for birthweight in females to be influenced by the presence of a male co-twin. This is in agreement with two other studies (Goldman et al, 2003;Orlebeke et al, 1993).…”
Section: Discussionsupporting
confidence: 94%
“…We did not find a tendency for birthweight in females to be influenced by the presence of a male co-twin. This is in agreement with two other studies (Goldman et al, 2003;Orlebeke et al, 1993).…”
Section: Discussionsupporting
confidence: 94%
“…Our findings are in line with previous studies showing a difference of 57 g 10 , 64 g 11 and 78 g 12 , even when different inclusion criteria for SS twins were used. For girls, birth weight was very similar in SS and OS twins, which is also in agreement with these studies 10 12 . Boys with a co-twin sister were 0.16 cm longer than those with a co-twin brother, but differences were not significant in girls.…”
Section: Discussionsupporting
confidence: 93%
“…Some studies have shown that boys from opposite-sex (OS) pairs are significantly heavier at birth than boys from same-sex (SS) pairs 10 12 , but this difference did not reach significance in other studies 13 – 16 . The greater birth weight of boys from OS pairs has generally been ascribed to a more successful in utero competition for nutrients of boys in the presence of a sister rather than a brother co-twin 17 .…”
Section: Introductionmentioning
confidence: 91%
“…A population-based study [7] then showed that females in unlike-sex twin pairs are signifi cantly heavier than females from like-sex pairs or female singletons, implying that an inter-twin mediator might exist; produced by the male that somehow affects the female co-twin despite the presence of a dichorionic placenta. Blumrosen and her co-workers [3] suggested that in severely discordant twins, the larger females were not signifi cantly heavier, an observation which might support the hypothesis of some form of gender-dependent intertwin infl uence.…”
Section: Introductionmentioning
confidence: 99%